Turkish Version of Evaluation of Ankylosing Spondylitis Quality of Life Questionnaire in Patients With Ankylosing Spondylitis: A Validation and Reliability Study - Nagehan ÖNCÜLOKUR; Dilek KESKİN and Yeşim GARİP and Hatice BODUR and Kenan KÖSE (Archives of Rheumatology, 2018)
Objectives: This study aims to translate the Evaluation of Ankylosing Spondylitis Quality of Life (EASi-QoL) into the Turkish language and test its validity and reliability. Patients and methods: A total of 100 AS patients (74 males; 26 females; mean age 38.2±9.9 years; range 21 to 63 years) were included. The mean disease duration was 115.9±91.6 months. EASi-QoL was translated from English into Turkish, and synthesis, back translation, revision, and pretest stages were performed. All patients were asked to complete the Turkish version of EASi-QoL. The internal consistency of EASi-QoL was determined with Cronbach’s alpha coefficient, and test-retest reliability was assessed by calculating the intra-class correlation coefficient. Confirmatory and explanatory factor analyses were performed to assess structural validity. Construct validity was also investigated by comparing the results of EASi-QoL with the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Ankylosing Spondylitis Disease Activity Score, Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), and AS-specific QoL scale. Results: Cronbach’s alpha coefficient was 0.910 in the physical function category, 0.893 in the disease activity category, 0.935 in the emotional well- being category, and 0.930 in the social contribution category (α>0.7). Factor loadings of all items in EASi-QoL were higher than 0.7, indicating the high reliability of the questionnaire. There was also a strong positive correlation between all subcategories of EASi-QoL (physical function, disease activity, emotional well-being and social participation) and AS-specific QoL scale, BASDAI, Bath BASFI, patient’s global assessment and pain severity. MASES and BASMI showed a moderate correlation with emotional well-being and social participation categories of EASi-QoL. Conclusion: Turkish version of EASi-QoL is a reliable and valid scale that can be used in clinical practice to evaluate QoL in detail in patients with AS.